Analysis of Aceh TV Programs in An Effort to Preserve Aceh Culture - Zulqaidah; Zainuddin T; Arif Ramdan (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2019)
The problems contained in the problem formulation are (1) What is the vision and mission of Aceh TV. And how Aceh TV realizes the vision and mission. (2) What programs are aired by Aceh TV related to the preservation of Aceh culture. (3) Does the program broadcast by Aceh TV support the preservation of Aceh culture. The purpose of this research is to find out the vision and mission of Aceh TV, and how Aceh TV realizes the vision and mission in preserving Aceh culture. To find out the programs aired by Aceh TV related to the preservation of Aceh culture, and also to find out whether the programs broadcast by Aceh TV support the preservation of Aceh. This type of research is qualitative research with data collection techniques namely observation, interviews, and documentation. The results of this study found that Aceh TV in realizing its vision and mission is by re-exploring Aceh's cultural values, so that people can learn about the culture. Aceh TV programs aired related to the preservation of Aceh culture, namely Ca'e Bak Jamboe, Meudikee, Ratoh, Seumapa, Seumeubeut, Piasan Aceh, Akai Bang Rusli and Keberni Gayo. The programs broadcast by Aceh TV support the preservation of Aceh's culture. And these programs are also still within the limits of Islamic law. The recommendations in this study are that Aceh TV is expected to add more programs related to culture. It is hoped that Aceh TV can reduce the Aceh song playback program, and it is also hoped that Aceh TV can improve the quality of the programs aired.